Allogeneic Hematopoietic Stem Cell Transplantation for Children With Acute Lymphoblastic Leukemia: Shifting Indications in the Era of Immunotherapy - Truong, Tony H.; Jinca, Cristian; Mann, Georg; Arghirescu, Smaranda; Buechner, Jochen; Merli, Pietro; Whitlock, James A. (Frontiers in Pediatrics, 2021)
Pediatric acute lymphoblastic leukaemia generally carries a good prognosis and most children will be cured and become long term survivors. However, a portion of children will harbor high-risk features at the time of diagnosis, have a poor response to upfront therapy or suffer relapse necessitating more intensive therapy, which may include allogeneic haematopoietic stem cell transplant (HSCT). Recent advances in risk stratification, improved detection and incorporation of minimal residual disease (MRD), and intensification of upfront treatment have changed the indications for HSCT over time. For children in first complete remission, HSCT is generally reserved for those with the highest risk of relapse. These include patients with unfavorable features/cytogenetics who also have a poor response to induction and consolidation chemotherapy, usually reflected by residual blasts after prednisone or by detectable MRD at pre-defined time points. In the relapsed setting, children with first relapse of B-cell ALL are further stratified for HSCT depending on the time and site of relapse while all patients with T-cell ALL are generally consolidated with HSCT. Alternatives to HSCT have also emerged over the last decade including immunotherapy and chimeric antigen receptor (CAR) T-cell therapy. These novel agents may spare toxicity while attempting to achieve MRD-negative remission in the most refractory cases and serve as a bridge to HSCT. In some situations, these emerging therapies can indeed be curative for some children with relapsed or resistant disease, thus obviating the need for HSCT. In this review, we seek to summarize the role of HSCT in the current era of immunotherapy.